Pure gold from the words of Sayyidī ʻAbd al-ʻAzīz al-Dabbāgh =al-Dhabab al-Ibrīz min kalām Sayyidī ʻAbd al-ʻAzīz al-Dabbāgh - Sijilmāsī, Aḥmad ibn al-Mubārak, d. 1743. (Basic Texts of Islamic Mysticism, 2007)
Around 1720 in Fez Aḥmad born al-Mubārak al-Lamaṭī, a religious scholar, wrote down the words and teachings of the Sufi master ʿAbd al-ʿAzīz al-Dabbāgh. Al-Dabbāgh shunned religious studies but, having reached illumination and met with the Prophet Muḥammad, he was able to explain any obscurities in the Qurʾān, ḥadīth s and sayings of earlier Sufis. The resulting book, known as the Ibrīz , describes how al-Dabbāgh attained illumination and access to the Prophet, as well as his teachings about the Council of the godly that regulates the world, relations between master and disciple, the darkness in men's bodies, Adam's creation, Barzakh, Paradise and Hell, and much more besides. This 'encyclopaedia' of Sufism with its many teaching stories and illustrations provides a window onto social life and religious ideas in Fez a generation or so before powerful outside forces began to play a role in the radical transformation of Morocco.